(F)Utility of invasive haemodynamic measurements to guide percutaneous intervention in chronic coronary artery disease (Swiss Medical Weekly, 2015)
Percutaneous coronary intervention (PCI) in chronic stable coronary artery disease has not been shown to reduce the incidence of myocardial infarction or death. There is, however, evidence that the outcome from PCI is dependent on the amount of myocardial ischaemia. This review provides an overview of coronary circulatory pathophysiology and focuses on fractional flow reserve from a semantical, conceptual and practical point of view.